2000
DOI: 10.1101/sqb.2000.65.21
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Mutation in Escherichia coli

Abstract: In 1988 John Cairns, Julie Overbaugh, and Stephan Miller published a paper entitled "The origin of mutants," in which they suggested that bacteria could choose which mutations to make (11). Shortly thereafter, Cairns and I began collaborating on a National Science Foundation-funded project to investigate the genetic basis of what was popularly called "directed mutation" (although at the time we were calling it "selectiondependent mutation," which now seems as good a name as any). Our plan was to mutagenize an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 88 publications
(35 reference statements)
1
92
2
Order By: Relevance
“…The mechanism of adaptive Lac + mutation in FC40 has been recently reviewed [46]. The following is a summary of the relevant characteristics:…”
Section: The Genetics Of Adaptive Mutationmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of adaptive Lac + mutation in FC40 has been recently reviewed [46]. The following is a summary of the relevant characteristics:…”
Section: The Genetics Of Adaptive Mutationmentioning
confidence: 99%
“…The rate of adaptive mutation is reduced two-to four-fold if Pol IV is eliminated [57,58]. E. coli's other inducible error-prone polymerase, Pol V, is not involved in adaptive mutation [36,59].…”
Section: The Genetics Of Adaptive Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to Pol V, Pol IV is abundant even in normally growing cells (∼250 molecules) and can be induced 10-to 30-fold by DNA damage and other stresses (25,26). Pol IV is required for stationary-phase or adaptive mutation (27,28) and has a substantial role in producing mutations on the F´episome (29,30). However, in normally growing cells Pol IV contributes only 10%, at most, to spontaneous mutations on the chromosome (20,29,31).…”
Section: Significancementioning
confidence: 99%
“…The molecular details of the mechanism responsible for this mutagenesis are quite controversial, but the involvement of dinB is well-established. [41][42][43][44][45][46][47][48][49] The fact that deletion of the chromosomal dinB gene does not profoundly alter spontaneous mutagenesis suggests that DinB function may not always be mutagenic. Indeed, it has been suggested that the -1 frameshift phenotype observed in adaptive mutagenesis arises as a consequence of its substrate specificity 50 and the increased levels of DinB produced from the episomal copy.…”
Section: Adaptive Mutagenesismentioning
confidence: 99%